The Influence of Doping with Transition Metal Ions on the Structure and Magnetic Properties of Zinc Oxide Thin Films - Jenica Neamtu; Marius Volmer (The Scientific World Journal)
Zn1−xNixO (x=0.03÷0.10) and Zn1−xFexO (x=0.03÷0.15) thin films were synthesized by sol-gel method. The structure and the surface morphology of zinc oxide thin films doped with transition metal (TM) ions have been investigated by X-ray diffraction (XRD) and atomic force microscopy (AFM). The magnetic studies were done using vibrating sample magnetometer (VSM) at room temperature. Experimental results revealed that the substitution of Ni ions in ZnO wurtzite lattice for the contents x=0.03÷0.10 (Ni2+) leads to weak ferromagnetism of thin films. For Zn1-xFexO with x=0.03÷0.05, the Fe3+ ions are magnetic coupling by superexchange interaction via oxygen ions in wurtzite structure. For x=0.10÷0.15 (Fe3+) one can observe the increasing of secondary phase of ZnFe2O4 spinel. The Zn0.9Fe0.1O film shows a superparamagnetic behavior due to small crystallite sizes and the net spin magnetic moments arisen from the interaction between the iron ions through an oxygen ion in the spinel structure.